Assessing China's power sector low-carbon transition: A framing paper - Anders Hove (The Oxford Institute for Energy Studies, 2023)
China's low-carbon energy transition depends on the power sector taking the lead. In this assessment, we seek to answer three questions about China's power sector transformation: (1) Is the power sector transition on track, in terms of non-fossil and renewable capacity and output? (2) Are market reforms in the power sector a prerequisite for China's low-carbon transition? (3) Do efforts at international experience sharing and topics of cooperative research require adjustment? The paper assesses that China is making steady progress at decarbonising in some sectors, such as the power sector and transport, while others will require more time to assess. On market reforms, however, progress has been slow and appears likely to remain so. While to date, international cooperation on power sector cooperation has focused on evaluating the potential benefits of a target market model in China, the paper argues that efforts to highlight progress in technology or policy - both inside and outside China - may have greater impact on future policy discussions.
Keywords: 330; China; Coal; decarbonisation; net-zero; Power Sector; Reform; Renewables